Experimental demonstration of extended depth-of-field f/1.2 visible High Definition camera with jointly optimized phase mask and real-time digital processing - Burcklen M.-A.; Diaz F.; Leprêetre F.; Rollin J.; Delboulbé A.; Lee M.-S. L.; Loiseaux B.; Koudoli A.; Denel S.; Millet P.; Duhem F.; Lemonnier F.; et al. (Journal of the European Optical Society-Rapid Publications, 2015)
Increasing the depth of field (DOF) of compact visible high resolution cameras while maintaining high imaging performance in the DOF range is crucial for such applications as night vision goggles or industrial inspection. In this paper, we present the end-to-end design and experimental validation of an extended depth-of-field visible High Definition camera with a very small f-number, combining a six-ring pyramidal phase mask in the aperture stop of the lens with a digital deconvolution. The phase mask and the deconvolution algorithm are jointly optimized during the design step so as to maximize the quality of the deconvolved image over the DOF range. The deconvolution processing is implemented in real-time on a Field-Programmable Gate Array and we show that it requires very low power consumption. By mean of MTF measurements and imaging experiments we experimentally characterize the performance of both cameras with and without phase mask and thereby demonstrate a significant increase in depth of field of a factor 2.5, as it was expected in the design step.